2021
DOI: 10.3390/cancers13215317
|View full text |Cite
|
Sign up to set email alerts
|

Delivery Capacity and Anticancer Ability of the Berberine-Loaded Gold Nanoparticles to Promote the Apoptosis Effect in Breast Cancer

Abstract: Gold nanoparticles (AuNPs) were fabricated with biocompatible collagen (Col) and then conjugated with berberine (BB), denoted as Au-Col-BB, to investigate the endocytic mechanisms in Her-2 breast cancer cell line and in bovine aortic endothelial cells (BAEC). Owing to the superior biocompatibility, tunable physicochemical properties, and potential functionalization with biomolecules, AuNPs have been well studied as carriers of biomolecules for diseases and cancer therapeutics. Composites of AuNPs with biopolym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…Additionally, AuNPs can be functionalized with targeting molecules, such as antibodies or aptamers, allowing for targeted drug delivery to specific cell types or tissues [ 61 ]. Additionally, our studies have verified that AuNPs modified with collagen are a biocompatible nanodrug delivery system that can carry natural compounds and has demonstrated good anti-cancer capacities [ 18 , 62 ]. However, since the higher concentration of AuNP may lead to cytotoxicity, the mission to select appropriate concentration of nanoparticles to develop a nanodrug delivery system becomes important for regenerative therapies [ 40 ].…”
Section: Discussionmentioning
confidence: 86%
“…Additionally, AuNPs can be functionalized with targeting molecules, such as antibodies or aptamers, allowing for targeted drug delivery to specific cell types or tissues [ 61 ]. Additionally, our studies have verified that AuNPs modified with collagen are a biocompatible nanodrug delivery system that can carry natural compounds and has demonstrated good anti-cancer capacities [ 18 , 62 ]. However, since the higher concentration of AuNP may lead to cytotoxicity, the mission to select appropriate concentration of nanoparticles to develop a nanodrug delivery system becomes important for regenerative therapies [ 40 ].…”
Section: Discussionmentioning
confidence: 86%
“…Qin et al found that a conjugator via linker BBR to platinum (II) complex significantly improved the in vitro and in vivo anti-BC activity (134). In addition, drug delivery using nanocarriers is widely used to improve cell penetration, biocompatibility, and in vivo efficacy, and this method is also an applicant for improving bioavailability and the efficacy of BBR against BC (135)(136)(137). Moreover, chemical modification is also a potent strategy to improve cell penetration, and water soluble anti-tumor activity of BBR and several BBR derivatives have been designed and exhibited better anti-BC efficacy than their lead compound BBR (132,(138)(139)(140)(141).…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis was responsible for the decreased progression of breast tumor by berberine-loaded gold nanoparticles, and upregulation of Bax and p21 were observed. 31 The resveratrol-loaded gold nanostructures had 30.75 nm size and −32.8 mV zeta potential. The resveratrol-loaded gold nanoparticles suppressed the growth and metastasis of breast cancer cells via through suppressing MMP-9 and COX-2.…”
Section: Phytochemicalsmentioning
confidence: 98%
“…Berberine was loaded onto gold nanoparticles and they were internalized through clathrin‐mediated endocytosis and autophagy, and they significantly decreased the viability. Apoptosis was responsible for the decreased progression of breast tumor by berberine‐loaded gold nanoparticles, and upregulation of Bax and p21 were observed 31 . The resveratrol‐loaded gold nanostructures had 30.75 nm size and −32.8 mV zeta potential.…”
Section: Drug Deliverymentioning
confidence: 99%